Efektivitas dan Efisiensi Realisasi Anggaran Belanja pada Pemerintah Kabupaten Gresik - Rahmadhany Hadi Kusuma; Gideon Setyo Budiwitjaksono (IPM2KPE, 2023)
This research aims to analyze the financial performance of the Gresik Regency Government for the 2017 - 2021 budget year using a financial performance assessment based on the calculation of effectiveness and efficiency ratios in the Budget Realization Report. This research uses a quantitative descriptive method and uses secondary data objects taken from the Regional Budget Realization Report. The results of this research as a whole illustrate that the financial performance of the Gresik Regency Government can be said to be good because it is within the effective and efficient criteria. The level of effectiveness of regional budget realization for the 2017-2021 fiscal year obtained an average percentage of 88.32% with the criteria being quite effective and the level of efficiency of direct expenditure in the 2017-2021 fiscal year obtained an average percentage of 49.94% with the criteria of being very efficient . In conclusion, the level of effectiveness of budget realization criteria is quite effective and the level of efficiency of direct spending is included in the criteria of very efficient. Keywords: Shopping Budget, APBD, Effectiveness, Efficiency